The effect of mothers' digital health literacy on fever management: The mediating role of perceived maternal self-efficacy - Uncu, Fatos; Evcimen, Hasan; Bulut, Elanur (Elsevier Science Inc, 2026)
Aim This study examined the mediating role of perceived maternal parenting self-efficacy in the relationship between digital health literacy and fever management in children. Methods A cross-sectional design was employed with 408 mothers of children aged 0-6 years in Eastern Turkey. Data collection was conducted through face-to-face interviews in a pediatric outpatient clinic using three validated scales: Digital Health Literacy Scale, Perceived Maternal Parenting Self-Efficacy Questionnaire, and Parent Fever Management Scale. Structural Equation Modeling with maximum likelihood estimation tested the hypothesized mediation model. Model fit was evaluated using multiple indices (chi(2)/df = 4.060, CFI = 0.911, RMSEA = 0.075), and bootstrapping with 5000 resamples assessed indirect effects. Results Digital health literacy demonstrated significant positive associations with both fever management (beta = 0.284, p = 0.001) and perceived maternal self-efficacy (beta = 0.370, p < 0.001). Perceived maternal self-efficacy was a strong predictor of fever management (beta = 0.233, p < 0.001). The mediation analysis revealed a significant indirect effect (beta = 0.087, 95 % CI [0.043, 0.136], p < 0.001), confirming partial mediation. Conclusions These findings highlight that digital health literacy influences fever management through dual pathways: directly, and indirectly through its effect on maternal self-efficacy. Healthcare interventions should integrate components that enhance both digital literacy and parenting confidence to optimize child health outcomes. Practical implications Pediatric nursing practice should incorporate assessments of digital health literacy and implement evidence-based strategies to build maternal competence, ultimately bridging the gap between health knowledge and practice in fever management. (c) 2026 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Digital health literacy; Perceived maternal parenting efficacy; Fever management; Children; Structural equation modeling